Development of theranostic probes for cervical cancer - Benson, Samuel John (The University of Edinburgh, 2021)
Myriad advances have been made in the prevention and diagnosis of cervical cancer during the 21st century, yet still thousands of women develop the disease every year. For those women diagnosed, mortality rates, especially in the global south, are high. Even for those women who enter remission, the consequences of surgical intervention can result in life-long complications surrounding fertility. Herein, the development of a novel treatment platform for cervical cancer was evaluated based on photodynamic therapy. Photodynamic therapy combines three non-toxic components; oxygen, light, and a photosensitiser to ablate cells via oxidative stress. Commencing with the evaluation of current offerings in the treatment of cervical cancer and photodynamic therapy, herein is described the development of a new family of fluorophores (SCOTfluors) which were adapted into the smallest photosensitizers to date. Subsequently these new photosensitisers were combined with a variety of targeting moieties including glucose and the peptide EMI-137-P, currently under development for targeting the c-Met receptor in relation to cancer, to bring about the selective ablation of cancerous tissue. It is hoped that these novel probes can be implemented for cervical photodynamic therapy, providing a minimally invasive and tissue sparing procedure for the treatment of cervical cancer.